2020
DOI: 10.28948/ngumuh.598289
|View full text |Cite
|
Sign up to set email alerts
|

Konya Kapali Havzasi (Türki̇ye) Yillik Sicaklik Veri̇leri̇ni̇n Trend Anali̇zi̇ Ve Deği̇şi̇m Noktalarinin Beli̇rlenmesi̇

Abstract: Climate change is expressed as major changes in the average climate which exist for many years. Although climate change occurs on a global scale, the impact of climate change varies from region to region. Therefore, the analysis of the variations in meteorological variables is a very vital issue in monitoring of climate change. In this study, assignment of the change points and trends of annual temperature (Tmean, Tmin and Tmax) data of the Konya Closed Basin in Turkey is examined. For this aim, air temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In past studies, homogeneity analysis was applied to the total precipitation, maximum, minimum, and average temperature series in different regions of Turkey. When we examine the studies conducted, we can observe that while the homogeneity of the temperature series has deteriorated (Ay, 2020;Yaman & Ertuğrul 2020), it is generally homogenous in the precipitation series , Hırca ve Eryılmaz Türkkan, 2020, Yaman & Ertuğrul 2020, Koycegız & Buyukyıldız 2020. These studies were found to be similar to the results of our results regarding the Van region.…”
Section: Discussionsupporting
confidence: 83%
“…In past studies, homogeneity analysis was applied to the total precipitation, maximum, minimum, and average temperature series in different regions of Turkey. When we examine the studies conducted, we can observe that while the homogeneity of the temperature series has deteriorated (Ay, 2020;Yaman & Ertuğrul 2020), it is generally homogenous in the precipitation series , Hırca ve Eryılmaz Türkkan, 2020, Yaman & Ertuğrul 2020, Koycegız & Buyukyıldız 2020. These studies were found to be similar to the results of our results regarding the Van region.…”
Section: Discussionsupporting
confidence: 83%
“…The existence of an increasing trend in annual temperature records has been ascertained by various trend analysis methods in the Central Anatolia region and the Kizilirmak River basin [21,25,39,[43][44][45][46][47][48].…”
Section: Figure 4 S-mk Results Of Stationsmentioning
confidence: 99%
“…They stated that the temperatures in the region are in an increasing trend. Köyceğiz and Buyukyildiz [21] researched the trends of annual average temperature, maximum temperature and minimum temperature data of Konya Closed Basin, stating that more than 80% of the annual temperature series has a statistically significant increasing trend.…”
Section: Introductionmentioning
confidence: 99%